Customer Relationship Systems and Business Models - Kaderják, Gyula (Acta Agraria Debreceniensis, 2009)
The object of this study is a comprehensive review of customer relationship management (CRM) systems applied increasingly in several fields of economy. The CRM is not merely a subsequent software technology and application in the field of Business Intelligence, but rather a novel, comprehensive customer-centric approach to an organization’s philosophy in dealing with its customer for the sake of realization of short- and long-range business target contrary to the traditionally widespread productcentric approach. The object of the study, following a shortsynopsis of the theoretical and practical aspects of the CRM systems, is to analyse the range of the actual and potential users and to survey the CRM market. It will be analysed the scope of CRM supported business activities and processes, the terms and possible methods of launching and will be outlined a feasible model, too. The aim of conspectus of different CRM strategies (layers) is to reveal the urging need of turning approach in the field of management.